Education, skill development and sustainable livelihoods: Situation assessment of India's drug treatment and rehabilitation centres - Reid, G.; Tellis, E.; Kumar, S.; Higgs, Peter (IOS Press, 2017)
Background: Research into education and skill development of drug users to facilitate social and economic inclusion has not previously occurred in India. Objective: This paper examines education and skill development in government, NGO and private drug treatment and rehabilitation facilities of India. Methods: A mapping exercise was undertaken to identify drug treatment and rehabilitation facilities. A total of 119 responses received and one-third of drug users were described as illiterate or had achieved primary school only. Results: The majority of facilities did not provide basic education but virtually all provided HIV and drug education. A majority of facilities did not provide vocational education and livelihood skills and referrals to others for education and skills development were not common. Conclusion: To ensure and promote the social and economic re-integration of drug users into the community the provision of vocational education and skill development opportunities compatible with the needs of the society should be encouraged.